Predictors of Workplace Well-Being for Dual-Earner Couples During Covid-19 Pandemic - Gisela Oktaria Efi; Endang Parahyanti (Gadjah Mada Journal of Psychology (GamaJoP), 2021)
The Covid-19 pandemic has changed the life order of entire community including employees from dual-earner families. Overlapping roles experienced can cause tension and trigger work-family conflicts that can impact workplace well-being. Previous studies had often focused on well-being in general and there was a lack of research related to well-being in dual earner couples during pandemic. This study investigated the predictor role of core self-evaluation and spousal support through mediating role of work family conflict (WFC) on workplace well-being. Based on the conservation of resources theory, we need to identify essential resource to fulfill workplace well-being. Data were collected from 200 employed Jakarta Metropolitan area (Jabodetabek) dual-earners who had at least one child below the age of 13. According to the mediation with two predictors analysis, the mediating effect of WFC can only predict the linkage between core self-evaluation and workplace well-being (β = 0.02, SE =0.02; 95% CI [0.005, 0.061]) but cannot predict the role of spousal support through WFC on workplace well-being (β = 0.00, SE =0.00; 95% CI [-0.002, 0.007]). This finding explained the importance of self-evaluation during pandemic to enhance workplace well-being and buffered negative effect of work and family related burdens.